Identifying longitudinal trajectories of emotional distress symptoms 5 years after traumatic brain injury. (November 2014) - Sigurdardottir, S.; Andelic, N.; Roe, C.; Schanke, A. K.
Abstract Primary objective: To evaluate longitudinal trajectories of emotional distress symptoms after traumatic brain injury (TBI). Research design: Longitudinal study. Methods and procedures: Patients with mild-to-severe TBI, 118 patients participated at 3 months, 109 attended at 1-year and 89 attended the 5-year follow-up. Emotional distress was measured with the Impact of Event Scale-Revised. Patients were also assessed for coping style, anxiety, depression, substance abuse and trauma severity. Main outcomes and results: Based on growth mixture modelling, four trajectories of emotional distress symptoms were identified: 73.5% of patients were characterized by a pattern of resilience, 6.8% by a pattern of delayed distress, 14.6% by recovery and 5.1% by chronic distress. Relative to the resilience trajectory, avoidant-coping style and psychiatric problems were related to recovery and chronic trajectories. The delayed trajectory was similar to the resilience trajectory, except for elevated depressive and anxiety symptoms at 1- and 5-years. Demographics and injury-related variables were not significantly associated with emotional distress trajectories. Conclusions: Resilience was the most common trajectory following TBI. Patients characterized by recovery and chronic trajectories required attention and long-term clinical monitoring of their symptoms. Future research would benefit from longitudinal studies to analyse emotional distress symptoms and the strength of resilience over time.